2024 IFPRI audited financial statements - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
As we reflect on 2024 and look to the future, it is clear that IFPRI's mission remains vital, but food policy research must adapt to an evolving world. That landscape of global development and international cooperation is rapidly changing amid unabated conflicts, crises, misinformation, growing geopolitical uncertainties and, as we write this in May 2025, a sharp decline in development assistance and a shaken international trading system. Yet the fundamental need for high-quality evidence and independent policy analysis remains more critical than ever. Research-based, timely, and well-coordinated actions have the power to build communities that are healthier and more food secure, resilient, and sustainable worldwide.